2018
DOI: 10.1590/1981-22562018021.180083
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Contemporary Pilates method on physical fitness, cognition and promotion of quality of life among the elderly

Abstract: Objective: to evaluate the effects of the Contemporary Pilates method on the physical fitness, cognition and quality of life of the elderly. Method: the Senior Fitness Test battery, the Vienna Test System and the EUROHIS QOL-8 quality of life questionnaire were used. The study group consisted of 16 elderly people and 27 classes of the Solo Contemporary Pilates method, held twice a week. To verify the normality of the data the Shapiro-Wilk test was used while the physical fitness and cognition variables were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
2
0
5
Order By: Relevance
“…Among adolescents, physical activity may have beneficial effects on attention capacity and cognitive functions ( 37 , 38 ), and is likely to be effective in reducing depression symptoms amongst both adolescents and young adults ( 39 42 ). Meanwhile, different modes of exercise are investigated for the older population, including stretching exercise, such as Pilates ( 43 , 44 ) and Tai Chi Chuan ( 45 , 46 ), resistance exercise ( 26 , 47 ), multimodal exercise ( 48 50 ) and aerobic exercise ( 51 ). These modes of exercising seem to be similarly effective regarding cognitive improvement ( 23 ), but such improvement may not be seen in a short period of time ( 52 ).…”
Section: Physical Exercise and Agingmentioning
confidence: 99%
“…Among adolescents, physical activity may have beneficial effects on attention capacity and cognitive functions ( 37 , 38 ), and is likely to be effective in reducing depression symptoms amongst both adolescents and young adults ( 39 42 ). Meanwhile, different modes of exercise are investigated for the older population, including stretching exercise, such as Pilates ( 43 , 44 ) and Tai Chi Chuan ( 45 , 46 ), resistance exercise ( 26 , 47 ), multimodal exercise ( 48 50 ) and aerobic exercise ( 51 ). These modes of exercising seem to be similarly effective regarding cognitive improvement ( 23 ), but such improvement may not be seen in a short period of time ( 52 ).…”
Section: Physical Exercise and Agingmentioning
confidence: 99%
“…Gestational static and dynamic musculoskeletal alterations, such as decreased trunk mobility and altered movements, increased mass, and body dimensions 25 can lead to pain and discomfort, causing limitations in daily life and professional activities 26 . Therefore, PM can be an alternative for these problems, because it involves a synchronous work between body and mind 27 , providing direct and indirect effects on several aspects, from the prevention of health-related problems to physiological changes 28 , as is the case during the gestational period. In that sense, one of the studies 10 showed that PM was beneficial to improve the functional capacity of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Corroborando um estudo de coorte que utilizou a mesma bateria de testes a Senior Fitness Test (SFT), o qual mensura as aptidões físicas dos idosos, destacou a importante contribuição da manutenção e ganho de flexibilidade além de outras aptidões, como sendo condições relevantes no controle da saúde dos idosos, evitando assim as comorbidades associadas ao envelhecimento 16 .…”
Section: Discussionunclassified